Maximal sprinting speed of elite soccer players during training and matches - Djaoui, L.; Chamari, K.; Owen, A.; Dellal, A. (The Journal of Strength and Conditioning Research, 2017)
The aim of the present study was to compare (a) the maximal sprinting speed (MSS) attained by soccer players during matches (MSSmatch) according to their level of play (professional first French division vs. elite amateur fourth French division) and the playing positions and (b) the MSS attained by professional soccer players during 14 different types of small-sided games (SSG, MSSSSG) and match-play. All players monitored through the study performed a 40-m sprint test to assess individual MSS (MSStest) and compare it to the training and match activity, with the calculation of the percentage of MSStest (%MSStest) reached. No differences were found according to the level of play; however, positional wide players achieved a higher MSSmatch, %MSStest, and MSSSSG than central players (both defenders and midfielders) during matches and SSG. MSSmatch were higher than all MSSSSG, and MSSSSG were positively correlated with the area of the pitch (0.45, p < 0.001), its length (0.53, p < 0.001), and the number of players involved (0.38, p < 0.001). The closer SSG was to match situation in terms of rules, the higher the MSSSSG. Wide players reached higher MSS in match and SSG than central players, confirming the relevance of using SSG close to match situation to specifically prepare elite players to the maximal running speed demand of the match.